Influência da composição do concreto e dos parâmetros de ensaio na resistividade elétrica obtida pelo método direto - Farias, Lidianne do Nascimento (2020)
Electrical resistivity is seen as a parameter for verifying durability in structures, as it indicates the strength of concrete in terms of penetration by aggressive agents. In addition, considering it a non-destructive method, its use can be quite useful. However, this property can be influenced by several factors. In this context, the present study evaluated the behavior of electrical resistivity due to changes in the composition of mixtures (types of cement, water/cement ratios and gravel contents) and in terms of test parameters (moisture content, sample size, age and levels cracking). The electrical resistivity of the concrete was obtained through the Direct Method, according to the procedures of the Spanish standard UNE 83988-1 (AENOR, 2008). This test method has characteristics that have not been much investigated by the brazilian scientific community. The results showed that the electrical resistivity of the concrete increased with the type of cement CPV-ARI, with the increase in the content of coarse aggregate and with the reduction of the a/c ratio. Regarding the size of the specimens and their degree of humidity, the reduction of these parameters caused a substantial increase in the resistivity of the concretes. Cracking levels showed that invisible cracks suggest a low variation in resistivity when stress levels are applied to specimens. Finally, this work determines reference values regarding the exposure of concrete to corrosion levels, proposing the Direct Method as a way of evaluating the electrical resistivity of concrete.